A Rare Complication of Biliary Stent Migration: Small Bowel Perforation in a Patient with Incisional Hernia - Özkan Yilmaz; Remzi Kiziltan; Oktay Aydin; Vedat Bayrak; Çetin Kotan (Case Reports in Surgery)
Endoscopic biliary stents have been recently applied with increasing frequency as a palliative and curable method in several benign and malignant diseases. As a reminder, although most of the migrated stents pass through the intestinal tract without symptoms, a small portion can lead to complications. Herein, we present a case of intestinal perforation caused by a biliary stent in the hernia of a patient with a rarely encountered incarcerated incisional hernia.